Protective effects of astragaloside IV on IL-8-treated diaphragmatic muscle cells - Wang, Li (Exp Ther Med, 2019)
The diaphragmatic fatigue that results from airflow obstruction is associated with the severe morbidity of patients with chronic obstructive pulmonary disease. Astragaloside IV (AS-IV) has antioxidant, anti-apoptotic and anti-inflammatory activities in various cell types. The present study aimed to evaluate the protective effects of AS-IV in diaphragmatic muscle cells. Diaphragmatic muscle cells extracted from neonatal rats were treated with a series of AS-IV concentrations (5, 10 or 20 mg/l) and the AKT inhibitor GSK690693 in the presence of interleukin-8 (IL-8). Cell proliferation and AKT phosphorylation were measured using Cell Counting Kit-8 and western blot assays, respectively. Cell apoptosis and reactive oxygen species (ROS) production were evaluated using flow cytometric analysis. Caspase activity and concentrations of proinflammatory factors (tumor necrosis factor-α, IL-6 and IL-8) were assessed using a caspase colorimetric assay and ELISA, respectively. IL-8 treatment resulted in decreased rates of cell proliferation and increased rates of AKT phosphorylation, cell apoptosis, caspase 3/9 activity, ROS production and proinflammatory factor production. AS-IV and GSK690693 treatment reversed the effects of IL-8. The effects of AS-IV were dose-dependent. The present results suggested that AS-IV is a candidate for the treatment of diaphragmatic fatigue due to its antioxidant, anti-apoptotic and anti-inflammatory activity.